2016
DOI: 10.1016/j.memsci.2016.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free ceramic-carbonate dual phase membrane reactor for hydrogen production from gasifier syngas

Abstract: Ceramic-carbonate dual phase dense membranes are a new group of inorganic membranes with perm-selective to CO 2 at high temperatures. This paper reports a new catalyst-free tubular membrane reactor to shift CO from the hot gasifier syngas to H 2 and CO 2 with simultaneous separation of CO 2. The membrane reactor is based on a samarium-doped ceria (SDC)-carbonate dual phase membrane which removes CO 2 facilitating conversion of CO to H 2 at high temperatures. The results show that catalytic-free membrane reacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…It could be observed that the CO 2 recovery value increased gradually from 0.96 to 10.38% when the temperature was elevated from 350 to 750°C. The trend is consistent with the results reported by Dong et al 13 The decrease in CO 2 recovery at lower feed temperature was due to the low permeance of CO 2 across the membrane. When the temperature was increased, the permeability increased as well.…”
Section: Resultssupporting
confidence: 92%
“…It could be observed that the CO 2 recovery value increased gradually from 0.96 to 10.38% when the temperature was elevated from 350 to 750°C. The trend is consistent with the results reported by Dong et al 13 The decrease in CO 2 recovery at lower feed temperature was due to the low permeance of CO 2 across the membrane. When the temperature was increased, the permeability increased as well.…”
Section: Resultssupporting
confidence: 92%
“…Compared with polymeric membranes, ceramic membranes, such as alumina (Al 2 O 3 ) and zirconia (ZrO 2 ) membranes, benefit from higher mechanical strength and thermal stability [ 6 , 7 ] and are suitable for application under harsh operating conditions. They have shown promising potential for membrane absorption [ 8 , 9 , 10 ], membrane reaction [ 11 ], membrane distillation [ 12 ], and other applications. Typical ceramic membranes are usually designed to have an asymmetric structure, so to combine high flux and high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed several high-performance ceramic–carbonate dual-phase (CCDP) membranes, which are high-temperature CO 2 separation materials with remarkable CO 2 permeance and theoretically infinite CO 2 selectivity. The CCDP membrane is composed of a porous oxygen ionic-conducting or mixed-conducting ceramic phase that serves as a support layer and a molten carbonate phase infiltrated into the support. These CCDP membranes have been applied to the membrane reactor process for steam reforming of methane with a catalyst and water gas shift without catalyst . The catalyst-free CCDP membrane reactor shows high thermal and chemical stability under the WGS reaction environment.…”
Section: Introductionmentioning
confidence: 99%
“…These CCDP membranes have been applied to the membrane reactor process for steam reforming of methane with a catalyst 10 and water gas shift without catalyst. 11 The catalyst-free CCDP membrane reactor shows high thermal and chemical stability under the WGS reaction environment. It offers a CO 2 flux of 2.7 × 10 −3 mol s −1 m −2 and CO conversion and CO 2 recovery of 26.1 and 18.7%, respectively, much higher than the conventional fixedbed reactor performance under identical conditions.…”
Section: Introductionmentioning
confidence: 99%